A Theory of Deception - Ettinger, David
"This paper proposes an equilibrium approach to belief manipulation and deception in which agents only have coarse knowledge of their opponent's strategy. Equilibrium requires the coarse knowledge available to agents to be correct, and the inferences and optimizations to be made on the basis of the simplest theories compatible with the available knowledge. The approach can be viewed as formalizing into a game theoretic setting a well documented bias in social psychology, the fundamental attribution error. It is applied to a bargaining problem, thereby revealing a deceptive tactic that is hard to explain in the full rationality paradigm."
Keywords: CONOCIMIENTO Y PODER; NEGOCIACIONES